Triazine-graphdiyne with well-defined two kinds of active sites for simultaneous detection of Pb2+ and Cd2+. Issue 2 (April 2022) - Guo, Xihong; Li, Ying; Huang, Huan; Wang, Dongmei; Cui, Rongli; Li, Jialiang; Zhao, Yidong; Wang, Dan; Yuan, Hui; Dong, Jinquan; Sun, Baoyun
Abstract: Graphdiyne-based materials are promising candidates for the adsorption and detection of heavy metal ions (HMIs) as the acetylenic links in graphdiyne strongly interact with some metal ions. To improve the sensing performance of graphdiyne-based materials and further understand their detection mechanism, we prepared N-substituted graphdiyne (TGDY) through bottom-up method as electrode modified materials, which contained position-fixed and content-controlled alkynyl bonds and pyridine N atoms. By comparing with the H-substituted graphdiyne (HGDY), which was roughly the same in structure as TGDY except that the benzene ring without N atoms, we found that the introduction of N in TGDY greatly improves the electrochemical performance and the signal intensity is closely related to the number of detection sites. Furthermore, the performance of TGDY-based electrochemical sensor was also explored, which showed satisfactory selectivity, reproducibility, stability and applicability for the detection of Cd 2+ and Pb 2+ in water. Our work provided an important reference for rational design and synthesis of electrode materials through bottom-up method to improve the detection performance and explore the detection mechanism. Graphical Abstract: ga1 Highlights: TGDY with accurate type and content active sites is synthesized for sensing. TGDY is firstly used for the detection of Cd 2+ and Pb 2+ with excellent performance. Both alkynyl and N atoms serve as recognition sites for heavy metal ions. The density of active sites is closely related to detection performance.